HYDROXYL IN DIOPSIDE OF DIAMOND-FREE ULTRAHIGH-PRESSURE DOLOMITIC MARBLE FROM THE KOKCHETAV MASSIF, KAZAKHSTAN - Kikuchi M.; Ogasawara Y. (My University, 2006)
Hydroxyl (OH) content in diopside of one diamond-free ultrahigh-pressure (UHP) marble from the Kokchetav Massif, Kazakhstan, was estimated by a micro- Fourier transform infrared (FTIR) spectrometer. Two intrinsic diopside OH bands of FTIR absorption spectra were identified at 3645 and 3465 cm-1, with the former band dominating the spectra. Another band occurred at 3685 cm-1, which seemed to be accompanied by trivial bands at 3750, 3730, 3585, and 3565 cm-1. Intensity variation of the 3685 cm-1 band within a single diopside crystal and its location may suggest that the cause of this band was submicroscopic amphibole lamellae. The OH concentration of diopside was estimated to be no less than 850 ppm by weight. Using the previously published experimental data, this OH content indicates that diopside formed at pressures >5 GPa and in a high water activity (aH2O) environment. © 2006 Geological Society of America.
Keywords: DIAMOND-FREE UHP DOLOMITIC MARBLE; FTIR; HYDROXYL IN DIOPSIDE; KOKCHETAV MASSIF